Analysis of Changes in Distribution of Urban Heat Island in Medan City and its Relationship with Land Change using Remote Sensing Data - Pisyam, Altha Nurzafira Melin (Universitas Pendidikan Indonesia, 2024)
Medan City is the third largest metropolitan city in Indonesia and is the capital of the province of North Sumatra. As one of the cities of the National Activity Center (PKN), the city of Medan has considerable consequences for the rapid development of the city. The rapid development of cities has implications for increasing residential areas, reducing green land cover, means of transportation, energy consumption and production resulting in surface temperature conditions. The surface temperature of Medan City resulting from an increase in built-up areas, reduced green land cover, means of transportation, energy consumption and production is higher than areas covered by vegetation. The difference in temperature between Medan, which is densely built and areas that are still covered with vegetation, is called the UHI phenomenon. The objectives of this study are: (1) To analyze the distribution of changes in the UHI phenomenon in Medan City in 2013 and 2022 (2) To analyze the relationship of land use change to UHI in Medan City. The research method is LST data analysis to obtain UHI, NDVI and NDBI values . NDVI and NDBI values are also extracted using remote sensing data. The data used are Landsat 8 imagery in 2013 and Landsat 9 imagery in 2022. Analysis of the determination of influence is carried out using simple regression. The results of this study show that the distribution of UHI in Medan City from 2013 and 2022 generally has a similar distribution of UHI affected areas, namely the northern side of Medan City dominates which is a non-UHI area while the east, west and central sides are UHI affected areas.